Awareness of ergonomics among the engineering students / Rosley Jaafar, Amirul Akmal and Zuraira Libasin - Jaafar, Rosley; Akmal, Amirul; Libasin, Zuraira (Universiti Teknologi MARA, Perlis, 2020)
Ergonomics is helpful in both the prevention of occupational diseases and the promotion of health. It plays an important role in increasing work efficiency and productivity, which benefit the organization and the community. The purpose of this study is to find the level of ergonomics awareness among multidiscipline engineering students in Universiti Teknologi MARA (UiTM), Penang Malaysia. A questionnaire was developed and distributed to 246 engineering students and the responses were analyzed using the Statistical Package for the Social Sciences (SPSS) version 15. The results showed that the score of the average mean obtained for ergonomics awareness of ergonomics benefits and the effects if not practiced are 3.70 and 4.23 respectively which are considered high level. It means that they were well aware of ergonomics knowledge as much as possible to avoid getting injuries and health problems in the workplace. Therefore, it is essential to promote ergonomics principles and practices to the students as well as staff in UiTM more effectively. The UiTM Penang branch management can perform the ergonomic task group for staff and association for students to plan, handle, and monitor the awareness of ergonomics educational programs and activities to the staff and students.